Investigating optimal learning moments in U.S. and finnish science classes - Schneider, Barbara; Krajcik, Joseph; Lavonen, Jari; Salmela-Aro, Katariina; Broda, Michael; Spicer, Justina; Bruner, Justin; Moeller, Julia; Linnansaari, Janna; Juuti, Kalle; Viljaranta, Jaana (Journal of Research in Science Teaching, 2016)
This study explores how often students are engaged in their science classes and their affective states during these times, using an innovative methodology that records these experiences in situ. Sampling a subset of high schools in the U.S. and Finland, we collected over 7,000 momentary responses from 344 students over the course of a week. We examine engagement within and between students in different environments identifying common social and emotional factors they may be experiencing in their science classes, suggesting the challenges that the U.S. and Finland may encounter when implementing their new science standards (i.e., Next Generation of Science Standards and Finnish National Core Curriculum). We operationalize engagement as situational when students experience high levels of challenge, skill, and interest, which we term as optimal learning moments. Specifically we analyze: (i) the components of optimal learning; (ii) the relationship of optimal learning with other subjective measures; (iii) how optimal learning moments in science classes compare to other academic classes; and (iv) the extent that optimal learning moments predict an individual's perception of importance to self and future in science classes. Using several multivariate models, results show that when students are challenged in their classes and are appropriately skilled they are more likely to feel confident, successful, and happy during specific science classes as well as in other academic classes. When students experience more times of optimal learning in their science classes they are more likely to report that they perceive science as important to them and their futures. Females, however, report being more stressed in their science classes than males. © 2015 Wiley Periodicals, Inc. J Res Sci Teach 53:400–421, 2016